Revisiting employee motivation and job satisfaction within the context of an emerging economy: Theoretical representation and developing the model - Ncube, CM; Samuel, MO (My University, 2014)
The world’s economic attention is rapidly shifting towards the direction of emerging economies. In order to facilitate and accelerate this process, it is important that designated economic hubs are well positioned in terms of infrastructural and social development. This can only be achieved through an integrated human resource practices that recognises the importance of human beings (employees) as the most important factor for the success or failure of any social or economic project. This imperative therefore places employee motivation and job satisfaction in the forefront. It was against this background that this research was conducted to determine the level at which municipal employees of one of the world-class socio-economic cities in South Africa enjoyed job satisfaction using selected motivational variables. The study adopted a survey research method using quantitative research design. A measuring instrument with a Cronbach alpha coefficient of above 0.70 was developed and used to collect primary data from 300 employees of the municipal council. Main hypotheses were formulated and tested using both regression and correlation statistical analyses. Results show that intrinsic and extrinsic motivational variables impacted significantly on the level at which employees derived job satisfaction. Management can therefore develop a job satisfaction practice around identified motivational variables in order to maximise employee productivity and enhance quality service delivery.
Keywords: Intrinsic motivation; Extrinsic motivation; Metropolitan municipality; Emerging economy; Job satisfaction